2022
DOI: 10.1037/amp0000983
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in digital interventions.

Abstract: The notion of “engagement,” which plays an important role in various domains of psychology, is gaining increased currency as a concept that is critical to the success of digital interventions. However, engagement remains an ill-defined construct, with different fields generating their own domain-specific definitions. Moreover, given that digital interactions in real-world settings are characterized by multiple demands and choice alternatives competing for an individual’s effort and attention, they involve fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
66
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 148 publications
3
66
0
1
Order By: Relevance
“…Previous research underscores the necessity of mHealth apps that must be first accepted and used in an intended way to then achieve a desired health behavior change [ 3 , 19 ]. Correspondingly, previous research has identified factors affecting the uptake of and engagement with health and well-being smartphone apps [ 11 , 20 - 23 ]. Many of these strategies and factors, such as well-designed reminders, self-monitoring features, and embedded health professional support, have been applied across various health domains [ 11 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research underscores the necessity of mHealth apps that must be first accepted and used in an intended way to then achieve a desired health behavior change [ 3 , 19 ]. Correspondingly, previous research has identified factors affecting the uptake of and engagement with health and well-being smartphone apps [ 11 , 20 - 23 ]. Many of these strategies and factors, such as well-designed reminders, self-monitoring features, and embedded health professional support, have been applied across various health domains [ 11 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many definitions of engagement, most concur on its multifaceted and dynamic nature [ 23 , 25 ] suggesting that it subsumes the extent of intervention use (amount, frequency, and duration), as well as subjective experience (attention, interest, and affect) with the intervention [ 26 ]. Nahum-Shani et al [ 27 ] integrated theories of engagement across disciplines (ie, education, industrial or organizational psychology, and computer science) and suggested that engagement may be best thought of as “energy investment involving physical, affective, and cognitive energies directed toward a focal stimulus or task.” Recent examinations of engagement have indeed focused on a tripart model: behavioral (physical involvement with the intervention), cognitive (thinking about, attending to, and processing the intervention), and affective (emotional response to the intervention) [ 23 , 27 - 29 ]. These 3 domains are distinct; an individual can enjoy an intervention (affective) but not complete the suggested amount of use (behavioral), or they can complete intervention sessions (behavioral) and not make connections between the app and their life (cognitive).…”
Section: Introductionmentioning
confidence: 99%
“…These 3 domains are distinct; an individual can enjoy an intervention (affective) but not complete the suggested amount of use (behavioral), or they can complete intervention sessions (behavioral) and not make connections between the app and their life (cognitive). Nahum-Shani et al [ 27 ] asserted that engagement is a state that waxes and wanes because of a variety of internal and external factors [ 30 ] rather than a relatively stable construct [ 28 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations